Impact of Eye and Breast Shielding on Organ Doses During Cervical Spine Radiography: Design and Validation of MIRD Computational Phantom - Elshami, Wiam; Tekin, Huseyin Ozan; Issa, Shams A. M.; Abuzaid, Mohamed M.; Zakaly, Hesham M. H.; Issa, Bashar; Ene, Antoaneta (Frontiers in Public Health, 2021)
Purpose: The study aimed to design and validate computational phantoms (MIRD) using the MCNPX code to assess the impact of shielding on organ doses. Method: To validate the optimized phantom, the obtained results were compared with experimental results. The validation of the optimized MIRD phantom has been provided by using results of previous anthropomorphic phantom study. MIRD phantom designed considering parameters used in the anthropomorphic phantom study. A test simulation was performed to compare the dose reduction percentages (%) between the experimental anthropomorphic phantom study and MCNPX-MIRD phantom. The simulation was performed twice, with and without shielding materials, using the same number and locations of the detector. Results: The absorbed dose amounts have directly been extracted from the required organ and tissue cells parts of output files. Dose reduction percentages between the simulation with shielding and simulation without shielding were compared. The highest dose reduction was noted in the thymus (95%) and breasts (88%). The obtained dose reduction percentages between the anthropomorphic phantom study and the MCNPX-MIRD phantom were highly consistent and correlated values with experimental anthropomorphic data. Both methods showed Relative Difference (%) ranges between 0.88 - 2.22. Moreover, the MCNPX-MIRD optimized phantom provides detailed dose analysis for target and non-target organs and can be used to assess the efficiency of shielding in radiological examination. Conclusion: Shielding breasts and eyes during cervical radiography reduced radiation dose to many organs. The decision of not shielding patients should be based on research evidence as one size does not fit all.